A study on factors contributed toward neighborliness at Kampung Morten / Aisyah Balqis Hamdan and Nur Amira Suhaimi - Hamdan, Aisyah Balqis; Suhaimi, Nur Amira (Faculty of Administrative Science and Policy Studies, 2013)
This study will focus on three factors contribute toward neighborliness which are membership, social interaction and social cohesion. Membership define as one group individual that have stay in one place, and desire and volunteer crated the group to share interest and goals and same time work together to achieved what they desire too. The goals can be basic safety need and other. Besides that, social interaction means the society or community tendency to having communication each other in anywhere and anytime. Good interaction among community can created mutual trust and respect with each other. In other words, social cohesion can be existed if the community really understand what means by neighborliness. To build cohesion, this people need be reciprocal and cooperation. The voluntary is most important element that need to adopted in every community that live in neighborhood. It because from that, this people that have adopted with that element easy to given help and cooperated in doing any activities or program that bring benefit to all member of community. Thus, the main objective of this research is to study three factors which are membership, social interaction and social cohesion as independent variables contribute neighborliness among community as dependents variable at Kampung Morten. A study will conducted at Kampung Morten, the respondent is villager will answered the questionnaire given. The neighborliness among community at Kampung Morten was significant contributed by the three factors which are membership, social interaction and social cohesion. This research shown that there are significant relationship between factors that contributed neighborliness and the independent variables.